Experiences and needs of older patients with stroke in China involved in rehabilitation decision-making: a qualitative study - Zining Guo; Sining Zeng; Keyu Ling; Shufan Chen; Ting Yao; Haihan Li; Ling Xu; Xiaoping Zhu (BMC Medical Informatics and Decision Making)
Abstract Background Shared decision-making is recommended for stroke rehabilitation. However, the complexity of the rehabilitation modalities exposes patients to decision-making conflicts, exacerbates their disabilities, and diminishes their quality of life. This study aimed to explore the experiences and needs of older patients with stroke in China during rehabilitation decision-making, providing a reference for developing decision-support strategies. Methods A qualitative phenomenological design was used to explore the experiences and needs of older patients with stroke in China. Purposive sampling was used to recruit 31 older Chinese patients with stroke. The participants participated in face-to-face, semi-structured, and in-depth interviews. Data were analyzed using inductive thematic analysis. Results The key themes identified include (1) mixed feelings in shared decision-making, (2) multiple barriers hinder the possibility of participating in shared decision-making, (3) Delegating rehabilitation decisions to surrogates, (4) gaps between reality and expectation, and (5) decision fatigue from lack of continuity in the rehabilitation health care system. Conclusions Older patients with stroke in China have complex rehabilitation decision-making experiences and needs and face multiple obstacles when participating in shared decision-making. They lack an effective shared decision-making support system to assist them. Providing patients with comprehensive support (such as emotional and informational), strengthening the construction of a continuous rehabilitation system, alleviating economic pressure, and promoting patient participation in rehabilitation decision-making are necessary.